Appearance of Tumor Vessels in Patients With Choroidal Osteoma Using Swept-Source Optical Coherence Tomographic Angiography - Zhou, Nan; Xu, Xiaolin; Liu, Yueming; Wei, Wenbin; Peng, Xianzhao (Frontiers in Oncology, 2021)
Objective: To report the morphologic characteristics of tumor-related vasculatures and their association with secondary choroidal neovascularization (CNV), subretinal fluid (SRF), choroidal thickness, retinal pigment epithelium (RPE) alterations, subretinal hemorrhage and tumor decalcification in eyes with choroidal osteoma (CO), using swept-source optical coherence tomographic angiography (SS-OCTA). Design: Cross-sectional observational study. Participants: 33 eyes of 26 patients with a diagnosis of CO were recruited from April 1, 2020, to April 1, 2021. Methods: Applying SS-OCTA systems operating at 1050nm wavelengths, eyes with CO were imaged. Main Outcome Measures: Tumor-related vasculature in eyes with CO were characterized using multimodal imaging, and the images were anatomically aligned. Tumor thickness was manually measured as the distance between the upper boundary of the tumor and the underlying sclerochoroidal interface on the SS-OCT images. Subfoveal choroidal thickness was manually measured as the distance between the Bruch membrane and the sclerochoroidal interface on SS-OCT images. Results: Of the 26 Asian patients, 16 (62%) were women and 10 (38%) were men. The mean age was 26.8 years (median, 23; range, 8–45) years, and the mean best corrected visual acuity was 20/40. Thirty-three eyes underwent imaging and were diagnosed with CO. ICGA identified inhomogeneous hyperfluorescence due to tumor-related vasculature, and all corresponded to the structures that appeared as SFVNs combined with clusters of tangled vessels on SS-OCTA images. SFVNs were detected on SS-OCTA imaging in all eyes (100%) but not identified on ICGA. Of the 33 tangled vascular structures, 32 (97%) were located at the edge of or inner the tumor, and only 1 (3%) were associated with type 2 neovascularization. In addition, SS-OCT revealed SRF in 33 eyes (100%), 33 (100%) were located at the edge of CO, and only 1 was underlying macular. SRF with retinal edema in 30 of 32 eyes (94%). Conclusions: In eyes with CO undergoing SS-OCTA imaging, tumor vasculature appears as SFVNs associated with tangled vascular structures. The identification of actual tumor vasculature in patients with CO as SFVNs with inner or terminal vascular tangles rather than previously described CNV may help facilitate understanding of their pathogenesis, tumor control and response to treatment.